2010
DOI: 10.1007/s00268-010-0669-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Appendectomy in Adults with Complicated Appendicitis: Systematic Review and Meta‐analysis

Abstract: When compared to OA, laparoscopic appendectomy is advantageous in CA with regard to SSIs, with no significant additional risk of IAA (level 3a evidence).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
104
4
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(124 citation statements)
references
References 56 publications
8
104
4
8
Order By: Relevance
“…8 In patients with complicated appendicitis, it has been shown to reduce the rate of surgical site infection without a difference in post-operative intra-abdominal abscess formation. 12 The advantages of LA in male patients are less clear with a randomised trial from 2010 demonstrating no advantages and even an increased operative time compared to OA.…”
mentioning
confidence: 99%
“…8 In patients with complicated appendicitis, it has been shown to reduce the rate of surgical site infection without a difference in post-operative intra-abdominal abscess formation. 12 The advantages of LA in male patients are less clear with a randomised trial from 2010 demonstrating no advantages and even an increased operative time compared to OA.…”
mentioning
confidence: 99%
“…There was reported increase in incidence of intraabdominal abscess after LA [Peto odds ratio 1.87 (95 % confidence interval (CI) 1.19-2.93)] in 2010 Cochrane review [9], but in a systematic review, Markides et al reported this increase to be of no statistical significance [odds ratio (OR) 1.24 (95 % CI 0.84-1.84)] [10]. Intra-operative irrigation and suction continues to be a matter of debate.…”
Section: Appendicitismentioning
confidence: 99%
“…LA can be considered the gold standard in premenopausal women (LE 1a) [98], and it is feasible in the elderly (LE 3) [99] and the obese (LE 3) [100], but in men LA has no advantages compared with open appendectomy (OA) (LE 1b) [101]. Complicated appendicitis can be approached laparoscopically, with significant improvement of the surgical site (SS) infection rate (a minor advantage according to Clavien's criteria) (LE 3a) [102,103]. Thorough peritoneal lavage ( [6-8 L) and aspiration are recommended in complicated appendicitis (LE 5) in order to minimize the abscess formation rate [104].…”
Section: Acute Appendicitismentioning
confidence: 99%